New solitary wave solutions of the Sawada-Kotera equation and its bidirectional form. (12th July 2021) - Ghanbari, Behzad; Asadi, Esmaeel
Abstract: In this paper, the solitary wave ansatz method along with Hirota's bilinear form are used to study the well-known Sawada-Kotera equation and its bidirectional form. Numerical simulations related to some of these solutions are given in the article. These figures provide us with a better understanding of visualizing the dynamic behavior of solutions. For the latter equation, we have found an indefinite quadratic bilinear Hirota solution with three homogenous terms and a constant. The techniques used in this paper can be adopted to solve other nonlinear models.